Nanocantilever beams modeling, fabrication and applications - Voiculescu, Ioana; Zaghloul, M. E. (Mona Elwakkad) (Pan Stanford Publishing, 2016)
This book focuses on the fabrication and applications of cantilever beams with nanoscale dimensions. Nanometer-size mechanical structures show exceptional properties generated by their reduced dimensions. These properties enable new sensing concepts and transduction mechanisms that will allow the enhancement of the performance of devices to their fundamental limits. A number of scientists are conducting research in the area of nanocantilever beams. The book will particularly benefit researchers and help them consolidate their background in the field. The book aims to be an excellent scientific reference for an audience with diverse backgrounds and interests, including students, academic researchers, industry specialists, policymakers, and enthusiasts